A magyar börtönügy helyzete a kiegyezés korában különös tekintettel a rabjogok alakulására - Losonczi Eszter (2017)
Before the Austro-Hungarian Compromise of 1867, several penitentiaries were established in Hungary mostly due to the reforms initiated by the Austrian government. Due to the sad state of affairs, it was almost impossible to offer humane conditions in the majority of the penal institutions. Hedged with difficulties, the wardens tried to establish proper conduct towards the inmates in some of the penitentiaries. In the mid 19th century, forward-thinking ideas started to appear in the contemporary scientific literature. The authors of these articles were familiar both with the latest scientific concepts in the West but also with the underdeveloped domestic practice. Therefore, they could argue for the necessity of much-needed reforms and make proposals for the legislative. In 1867, the Hungarian Government was re-established by the King as part of the Compromise. The minister of justice made a report about the correctional system, which played a great role in the recognition of the issues in the penitentiary. The historical significance of this report lies in the fact, that many details regarding the Hungarian prison system were made available to the public for the first time. Its authors laid down some principles, like the classification of the inmates and the establishment of a unified prison system, through which they aimed to improve the conditions of the prisoners. They emphasized the importance of education and the cure of the convict’s souls, because they thought that these elements were necessary towards their resocialization. Regarding the responsibilities of the officers, the most basic principle was that they shall treat the inmates honourably. The prisoner’s rights also included the right to adequate amount of food and the right to work and to the education. Following the Austro-Hungarian Compromise, these proposals formed the basis of the forth-coming laws that laid down the foundation of the modern prison system.
Keywords: Társadalomtudományok; Jogtudomány